Para entender o repertório linguístico no ensino superior tecnológico: conversa entre a translinguagem e a educação sociocomunitária - Souza, Lilian de (2021)
This thesis presents the results of a research that investigated the role of named languages in Spanish learning, supported by translingual practices and socio-community education. The investigation took place in a context of teaching languages for specific purposes, in the Spanish class, inserted in the higher course of Events (formation of the Tourism, Hospitality and Leisure axis, acting in the organization and execution of events), at the Faculty of Technology of the State of São Paulo. The researcher observed, in foreign language classes, the incidence of the use of Portuguese during the activities, as well as other languages that are part of the linguistic repertoire of the students, thus, the Translanguaging theory was used in the studies developed by Canagarajah (2011) García (2014) and Li Wei (2017), who recognize the linguistic repertoire that each individual has to communicate, in a movement that transposes the languages with which they have contact, in order to make themselves understand and understand the other , regardless of the named language used. To help in the quest to understand the adaptations and uses of each subject's repertoire, Social and Community Education was used, which according to Bissoto (2012, 2016), Groppo (2013), Gomes (2008), Antônio (2012) and Miranda (2016) it is understood as a process of listening to different voices that configure the subjects, in an articulation between teaching and community, a socializing education. Translanguaging and Sociocommunity Education can compose a new discussion on education, as both highlight the need for the participation of the family and the community in the construction of knowledge, aiming at a society of greater equity. The research sought to investigate the role of the linguistic repertoire in Spanish learning from the perspective of translingual practices and socio-community education, in order to know how and at what time Brazilian students resort to the use of their mother tongue and/or other languages in the context of teaching languages for specific purposes, in addition to what would be the students' own perception of this phenomenon. The study follows an ethnographic-based qualitative methodology, which listens to the voice of all participants through an interview conducted by the researcher, on the analysis of the transcript of the virtual interaction carried out in pairs and which gave rise to the videos that comprised an evaluation activity of the subject. Data generation took place in four stages, namely: i) conducting a conversation in pairs recorded on video and sent to the teacher; ii) transcription of all recordings by the researcher teacher and subsequent return to the respective pairs; iii) reading and notes by students about the transcribed dialogue; iv) individual interview with each participant, in order to know their perceptions about the notes made both by the teacher and by themselves. The results of this investigation allowed a better understanding of the adaptations and the role of the Portuguese language, as well as the other languages that are part of the linguistic repertoire of students involved in foreign language learning.